Rasio Hutang Memediasi Pengaruh Rasio Laba Atas Aktiva dan Ukuran Perusahaan Terhadap Probabilitas Pembayaran Dividen Perusahaan Perkebunan Kelapa Sawit yang Listed di Bursa Efek Indonesia Periode Tahun 2010-2014 - Lumbantobing, Rudolf; Iskandar, Lie Robert (Manajemen Bisnis Kompetensi, 2017)
This study aims to investigate the influence of the debt policy, return on asset and firm size toward company’s dividend policy on listed oil palm plantation companies in Indonesia Stock Exchange during the years 2010-2014. The used data in this research was secondary data obtained directly from the company website and the Indonesia Stock Exchange. The data was analyzed using path analysis by using logistic regression analysis. The results showed that the profitability is significant and negative effect on the debt ratio. Size is not significant and positive on debt ratio. ROA is significant and positive effect on dividend policy. Size is significant and positive effect on dividend policy. The debt ratio is not significant positive effect on dividend policy. Dividend policy is influenced by leverage of the company. ROA has positively effect on dividend policy will be more negattive when DER increase, vice-versa. The positive effect of Size on dividend policy will not be more negative when debt ratios decline.Keywords: debt, company performance, firm size, dividend policy